The Effect of Durio Zibethinus L. Seed Extract on Fasting Blood Glucose and Insulin Resistance in Metabolic Syndrome Model Rats - Aisyah, Siti; Harioputro, Dhani Redhono; Nurwati, Ida (Politeknik Kesehatan Kemenkes Mamuju, 2024)
Metabolic syndrome is known as insulin resistance syndrome, characterized by chronic hyperglycemia. Management of metabolic syndrome involves several combinations, including lifestyle modifications and pharmacological interventions. Durian seeds are one source of antioxidants that have the potential to improve blood glucose homeostasis and insulin sensitivity. This study aims to analyze the effect of durian seed extract on changes in fasting blood glucose levels and insulin resistance. The extraction process utilized the maceration method with a 70% ethanol solution. This study consisted of 30 rats divided into six treatment groups: KN (normal group), K- (negative control), K+ (positive control metformin 9 mg/kgBW), P1, P2, and P3, which were given durian seed extract at doses of 100 mg/kgBW, 200 mg/kgBW, and 300 mg/kgBW, respectively. Metabolic syndrome rats were induced with a high-fat, high-fructose diet for 14 days, then induced with streptozocin (STZ) and nicotinamide (NA). Fasting blood glucose levels were determined using the GOD-PAP method. The HOMA-IR index was used to measure insulin resistance. The data results were evaluated using a paired T-test and one-way ANOVA. The analysis showed a significant variance in fasting blood glucose and HOMA-IR index following a 21-day treatment (p<0.05). The highest decrease was found in the 300 mg/kgBW dose group with fasting blood glucose and HOMA-IR index of 90.00 ± 2.70 mg/dl and 3.55 ± 0.11. The P2 and P3 treatments did not show different results with metformin treatment (p>0.05). The findings of this study suggest that consumption of durian seed extract for 21 days can effectively improve the condition of mice with metabolic syndrome. In addition, the drug metformin has the same effect as the intervention of durian seed extract doses of 200 and 300 mg/kgBW.